Comparison of Pre-emptive Tramadol versus Diclofenac in Postoperative Pain Management after Laparoscopic Cholecystectomy: Postoperative Pain Management - Nawaz, Ahmad; Ishrat, Zahra; Abdullah, Fatima; Rashid, Muhammad; Yousaf, Sohaib; Hameed, Salman (Pakistan Journal of Health Sciences, 2025)
Effective Pre-emptive analgesia is essential to improve pain control and reduce opioid consumption. Non-opioid analgesics such as diclofenac and tramadol are commonly used, but their comparative efficacy remains an area of interest. Objective: To compare mean postoperative pain intensity and time to 1st analgesic requirement between diclofenac and tramadol groups as Pre-emptive analgesics among patients undergoing laparoscopic cholecystectomy. Methods: This quasi-experimental study was conducted at Department of Anaesthesia, Mayo Hospital, Lahore, over period of six months. Quasi experimental study. 50 patients scheduled for elective laparoscopic cholecystectomy were included and randomized into two groups using lottery technique. Group D (diclofenac sodium 100mg), and Group T (oral tramadol 100mg), respective drug was given two hours before surgery. Postoperatively, NRS score were assessed at 8th hour, and time to first analgesic request was recorded. Data were analyzed using SPSS version 26.0, p-value ≤ 0.05 considered statistically significant. Results: Postoperatively, mean NRS score at 8th hour was significantly lower in Group T (3.56 ± 1.32) compared to Group D (4.52 ± 1.22) (p=0.01). Mean time to first analgesic request was significantly longer in Group T (104.04 ± 12.02 minutes) than in Group D (91.64 ± 8.51 minutes) (p<0.001). Conclusions: Preoperative administration of oral tramadol provides superior postoperative analgesia compared to diclofenac sodium, as evidenced by lower pain scores at the 8th postoperative hour and longer time to first analgesic request. Tramadol may be more effective option for pain control in patients undergoing elective laparoscopic cholecystectomy.